Isolation and preliminary characterization of two forms of ribulose 1,5-bisphosphate carboxylase from Rhodopseudomonas capsulata. - Gibson, J L (1977)
The presence of two distinct forms of ribulose 1,5-bisphosphate carboxylase has been demonstrated in extracts of Rhodopseudomonas capsulata, similar to the form I (peak I) and form II (peak II) carboxylases previously described from R. sphaeroides (J. Gibson and F. R. Tabita, J. Biol. Chem 252:943-949, 1977). The two activities, separated by diethylaminoethyl-cellulose chromatography, were shown to be of different molecular size after assay on polyacrylamide gels. The higher-molecular-weight carboxylase from R. capsulata was designated form I-C, whereas the smaller enzyme was designated form II-C. Catalytic studies revealed significant differences between the two enzymes in response to pH and the effector 6-phosphogluconate. Immunological studies with antisera directed against the carboxylases from R. sphaeroides demonstrated antigenic differences between the two R. capsulata enzymes; cross-reactivity was observed only between R. sphaeroides anti-form II serum and the corresponding R. capsulata enzyme, form II-C.